Strategies to counter transmission of “superbugs” by targeting free-living 3 amoebae - Siddiqui, Ruqaiyyah Bano *; Khan, Naveed Ahmed * (Elsevier, 2017)
Bacterial infections have remained significant despite our advances in the development of a plethora of disinfectants as well as antimicrobial chemotherapy. This is in part due to our incomplete understanding of the prevalence of bacterial pathogens in the environmental and clinical settings. Several lines of evidence suggest that Acanthamoeba is one of the most ubiquitous/resilient protists that also acts as a host/reservoir for pathogenic microbes. Thus targeting the hardy host, which harbour microbial pathogens, offer a potential avenue to counter infection transmission, particularly hospital/community-acquired infections. This will complement existing approach of applying disinfectants that are targeted against bacterial pathogens 10 directly.